Statistical Simulation of Patient Compliance - Song, Mikyung (My University, 1984)
Patient compliance is one of the important factors which effect patient outcome in therapeutic trials. As the methods of measuring patient compliance have been developed, the impact of compliance on therapeutic regimen performance could be studied. In this project, patient compliance measures are defined and compliance distributions are introduced. The two are combined from the two sources to improve both the knowledge of drug-outcome combinations and compliance information has been simulated in the case of therapeutic trials. The study of compliance effects on patient outcome was approached in two ways; looking at the fixed compliance effects upon the entire dose-response curve, and looking at the compliance measure as a variable effect on dose-response outcome of patients, the latter by means of statistical simulation. It was shown that patient compliance information affected patient outcome in terms of the achievement of the therapeutic goal. Also, the results of this project support what should be said about the basis of drug-outcome combinations and prescriptions, when we mention patient compliance. Another result is that Compliance-Response-outcome chains were obtained in terms of percentages to respond from simulation of some common design models used in therapeutic trials.
Keywords: patient; compliance; simulation